PERAN KEPEMIMPINAN MULTIKULTURAL DALAM MEMBENTUK KARAKTER SISWA DI ERA GLOBAL: STUDI KASUS SMK NEGERI 2 KARAWANG - Aulia Putri, Adelia; Hinggil Permana; Chairil Fajar Hadiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of multicultural leadership in shaping students’ character in the global era at SMK Negeri 2 Karawang. In the context of multicultural vocational education, school principals are required to possess inclusive and adaptive leadership skills in managing diversity and instilling character values such as tolerance, empathy, responsibility, and mutual respect. This study employs a qualitative approach using a literature review method, examining various scientific sources, school documents, and relevant previous studies. The results indicate that multicultural leadership at SMK Negeri 2 Karawang is implemented through interfaith religious activities, anti-discrimination policies, the integration of multicultural values into the learning process, and collaboration among schools, teachers, and parents. These strategies are able to create a harmonious learning environment that respects diversity and strengthens students’ character to become ethical, disciplined, and globally competitive individuals. This study confirms that multicultural leadership can serve as an effective model for developing character education based on diversity in the global era.